Does the cap fit? The case for contextualised Initial Teacher Training for vocational teachers - Bev Morris; Steve Gildersleve (Adult Education Research Conference, 2011)
This case study of UK teacher-training for vocational trainers highlights the tensions between the professionalization of the teaching workforce and the skills and expectations of vocational trainers.
Keywords: vocational teacher training